Quality in fruits of varieties of Carica papaya L. under organic management - Bibiano-Nava, Oscar; Hernández-Castro, Elías; Ariza-Flores, Rafael; Maldonado-Peralta, María de los Ángeles; Sarabia-Ruiz , Gregorio; Valenzuela-Lagarda, José Luis (Ecosistemas y Recursos Agropecuarios, 2021)
Papaya (Carica papaya L.) is one of the most important crops in Mexico, so it is essential to evaluate varieties that have better morphoagronomic and quality characteristics. The present research aims to evaluate the morphological, productive and physicochemical quality of the fruits of the papaya cultivars Maradona-F1, Bela Nova-F1 and Maradol under organic management in the dry tropics. The research was carried out at the Autonomous University of Guerrero, Costa Chica Regional Center for Higher Education, Florencio Villareal, Guerrero, Mexico. The Maradona-F1 cultivar presented the highest values ​​in maximum diameter (11.8 cm), however Maradol was higher in minimum diameter (9.0 cm). In maximum length, Maradona-F1 and Bela Nova-F1 expressed similar values ​​(21.9 cm; 21.9 cm), as well as in length at maximum diameter (14.7; 14.3 cm). In fruit weight it was expressed that Maradona-F1 presented 1447.0 g. In pulp thickness Maradona-F1 was greater (27.94 mm). The most intense value in L * was presented by Maradol, however, Bela Nova-F1 had the highest values ​​in a * (39.82) and b * (54.17). The highest percentage in titratable acidity was expressed by Bela Nova-F1 (0.14%). The highest pH was obtained by Maradol with a value of 5.89. In total soluble solids (° Brix) the hybrid Bela Nova-F1 expressed the highest value with 13.0 ° Brix. The Maradona F-1 and Bela Nova-F1 varieties have the best morphoagronomic and physicochemical characteristics, which makes them the most acceptable varieties for production in the dry tropics.